Meridional Overturning Circulation Observed by the Overturning in the Subpolar North Atlantic Program (OSNAP) Array from August 2014 to June 2020 - Fu, Yao; Lozier, M. Susan; Biló, Tiago Carrilho; Bower, Amy S.; Cunningham, Stuart; Cyr, Frédéric; de Jong, M. Femke; deYoung, Brad; Drysdale, Lewis; Fraser, Neil; Fried, Nora; Furey, Heather H.; et al. (Georgia Institute of Technology, 2023)
Strength of the Meridional Overturning Circulation across the OSNAP array, defined as the maximum of the streamfunction in density space; Meridional heat and freshwater transports; Overturning streamfunction in density space; Gridded velocity, temperature, and salinity across the OSNAP section. An international effort, Overturning in the Subpolar North Atlantic Program (OSNAP), is a partnership among oceanographers from the US, UK, Germany, the Netherlands, Canada and China whose goal is to measure and understand what drives the Atlantic Meridional Overturning Circulation (MOC) and its variability. OSNAP is consisted of about 60 moorings that stretch from Labrador to Greenland to Scotland, providing a continuous record of the full water column, trans-basin volume transports in the subpolar North Atlantic. The first 6 years of data (August 2014 - June 2020) from the full OSNAP array has been used to produce the monthly estimates of the MOC at OSNAP. All data are freely available from www.o-snap.org.